Preventive and Therapeutic Effects of Astaxanthin on Depressive-Like Behaviors in High-Fat Diet and Streptozotocin-Treated Rats - Ke, Yuting; Bu, Shizhong; Ma, Hong; Gao, Lei; Cai, Yujia; Zhang, Yisheng; Zhou, Wenhua (Frontiers in Pharmacology, 2020)
Coexistence of depression and diabetes has a negative impact on both lifestyle and quality of life. Astaxanthin (AST) has been demonstrated to improve the glucose metabolism and has antidepressant-like effect, but whether AST has the potential benefits for preventing depression in diabetes is still unknown. The aim of this study was to investigate the preventive and therapeutic effects of AST on the glucose metabolism or depressive-like behaviors in a diabetic rat model generated by feeding with a high-fat diet for 10 weeks followed by injection of 25 mg/kg STZ. Preventive treatment with AST was given at doses from 7.5, 15, 25 mg/kg/day by intragastric gavage daily for 4 weeks before STZ injection, preventive plus therapeutic treatment also given more 6 weeks after STZ injection, and therapeutic treatment only given for 6 weeks after one week of STZ injection. Depressive-like behaviors were evaluated at the end of the treatment by using open field, elevated plus-maze, locomotor activity and forced swimming tests. Preventive or therapeutic treatment with AST all reduced level of fasting glucose, improved glucose tolerance, decreased total TCh and TG in diabetic rats. Preventive or plus therapeutic treatment with AST decreased the immobility time, increased the time spend in the open arms and locomotor activity in diabetic rats, however, therapeutic treatment with AST failed to affect the depressive-like behaviors. Preventive or plus therapeutic treatment with AST at doses of 15 or 25 mg/kg increased significantly the expression of pERK, pAKT, pCREB, and BDNF in the PFC in diabetic rats respectively. In contrast, therapeutic treatment with AST at dose of 25 mg/kg increased only the expression of pERK in the PFC. The data demonstrated that AST may be used as the preventive or therapeutic approaches for co-morbidity of diabetes and depression.